Clinical Profile of Children with Mediastinal Tuberculosis. (20th August 2020) - Chunawala, Zainali; Shah, Ira
Abstract: Aim: To study clinical profile of children with mediastinal tuberculosis (TB). Methods: This retrospective study was undertaken between January 2015 and March 2018 in children diagnosed with mediastinal TB. Clinical history, examination and radioimaging, such as chest X-ray and HRCT chest, were done in every patient at the start of therapy. The prevalence of mediastinal TB was calculated. Factors associated with mediastinal TB and associated pulmonary TB (PTB) were analysed. Results: Out of total 1407 patients with TB, 58 (4.12%) had mediastinal involvement. Fever was seen in 49 (84.5%) patients, positive Mantoux test (MT) in 32 (68.1%), cough in 28 (48.3%), loss of appetite in 24 (41.4%) and weight loss in 17 (29.3%). Associated PTB was present in 22 (37.9%) patients. Associated extrapulmonary TB (EPTB) was observed in 12 (20.7%) patients. Fifty-one patients (87.9%) had an abnormal X-ray. Baseline HRCT chest was done in 54 (93.1%) patients and all of them showed necrotic caseous mediastinal nodes. Treatment duration of patients who completed treatment with first-line anti-tuberculous therapy was 11.67 months. Seventeen patients (29.3%) were diagnosed to have drug-resistant TB (DR-TB). Cough was seen more commonly in patients with associated PTB (68.2%) as compared to isolated mediastinal TB (36.1%) ( p = 0.0296). Conclusion: Mediastinal TB is common in children with EPTB. Associated PTB is seen in only about one-third of the patients. X-ray chest is abnormal in half the patients; hence, HRCT chest may be required to make a diagnosis. Bacteriological confirmation is necessary due to high incidence of DR-TB in these patients. Most of the patients require treatment for a longer duration as resolution takes a longer time. Computed tomography imaging on follow-up helps to determine the treatment duration.